An in vitro analysis of how lactose modifies the gut microbiota structure and function of adults in a donor-independent manner - Firrman, Jenni; Liu, LinShu; Mahalak, Karley; Hu, Weiming; Bittinger, Kyle; Moustafa, Ahmed; Jones, Steven M.; Narrowe, Adrienne; Tomasula, Peggy (Frontiers in Nutrition, 2023)
Following consumption of milk, lactose, a disaccharide of glucose and galactose, is hydrolyzed and absorbed in the upper gastrointestinal tract (GIT) for those that are lactose tolerant. However, hydrolysis and absorption are not always absolute, and some lactose will enter the colon where the gut microbiota has the ability to hydrolyze lactose and produce metabolic byproducts. In this study, the impact of lactose on the gut microbiota of healthy adults was examined, using a short-term, in vitro culturing strategy where fecal samples harvested from eighteen donors were cultured anaerobically with and without lactose. The data was compiled to identify donor-independent responses to lactose treatment. Metagenomic sequencing found that the addition of lactose decreased richness and evenness, while enhancing prevalence of the β-galactosidase gene. Taxonomically, lactose treatment decreased relative abundance of Bacteroidaceae and increased lactic acid bacteria, Lactobacillaceae, Enterococcaceae, and Streptococcaceae, and the probiotic Bifidobacterium. This corresponded with an increased abundance of the lactate utilizers, Veillonellaceae. These structural changes coincided with increased total short-chain fatty acids (SCFAs), specifically acetate, and lactate. These results demonstrated that lactose could mediate the gut microbiota of healthy adults in a donor-independent manner and provided insight into how dietary milk consumption may promote human health through modifications of the gut microbiome.